Designing fossil fuel subsidy reforms in OECD and G20 countries A robust sequential approach methodology - Elgouacem, Assia (OECD Environment Working Papers, 2020)
Reform of support for fossil fuels is often identified as a priority for a country's fiscal consolidation efforts and for climate action to align financial flows with low-carbon pathways. Its implementation, however, remains elusive for many countries as they face seemingly irreconcilable policy agendas of economic growth and sustainability coupled with potential political backlash against austerity and rising costs. This paper provides a sequential approach that may assist in providing support for the analysis to a well-informed reform process. Deploying the suggested tools can help policy makers to identify the most distorting government support measures and alternative or complementary policies that deliver the sought-after objectives more efficiently and effectively. The work presented here draws on the OECD's longstanding experience and tradition in measuring and tracking support measures for fossil fuels, primarily in its Inventory of Support Measures for Fossil Fuels (Inventory hereafter) and accompanying reports